Education, English and Social Empowerment – Banishing the Monster of Stratification from an Indian Classroom - Kaur, Jasjeet (THE PRIMARY TEACHER, 2006)
Universalisation of elementary education has often been seen as one of the esteemed goals towards the attainment of which the nation must work in complete solidarity. And indeed several sincere endeavours in this direction have registered optimum success. There has been a substantial rise in the literacy rate in the last two decades as a result of mass movements such as the total literacy campaign. The enrollment in various government run schools has also increased. But this spread of education has somehow failedto bridge the ever-widening gulf between the elite and the masses. It has left unaddressed, some of the cherished dreams and aspirations of the masses who should have benefited from these programmes. The aspirations of the underdogs of our society to enhance their standard of living or to seek an upward mobility through education are yet to materialise. Therefore, it is about time that we reassess